Strategi Komunikasi Program KBKM 2021 dalam Upaya Pemajuan Kebudayaan oleh KEMDIKBUD-RISTEK - Fridayani P, Septi (RESIPROKAL: Jurnal Riset Sosiologi Progresif Aktual, 2021)
One of the causes of the lack of cultural existence today is not because the level of awareness of the younger generation for culture is low or irrelevant, but because of the low level of communication between generations. The purpose of this study was to find out the communication strategy of the KBKM program in an effort to promote culture by KEMDIBUD-RISTEK RI to the younger generation. This research uses descriptive qualitative method with sample determination using purposive sampling technique and case study approach. Data collection techniques using interview and observation study methods and documentation using data validity triangulation techniques. The results of this study indicate that KEMDIKBUD-RISTEK RI has made efforts to promote culture through villages by attracting the role of young people using communication strategies from Onong Uchjana Effendy in the form of planning, management and implementation of communication. The planning includes the timeline and the publication process, communication management includes redundancy (repetition), canalizing, informative, persuasive, educative and also coercive. Then carry out the analysis of issues and the role of communication, selecting targets, determining targets, developing strategies and selecting partners, determining messages, determining communication tools, managing communication and conducting partner directions, planning activities, communication budgets, as well as monitoring and evaluation.